STRUKTUR EKONOMI DAN KETIMPANGAN PEMBANGUNAN EKONOMI ANTAR DAERAH DI PROVINSI SUMATERA BARAT - Easbi Ikhsan; Nadra Yudelsa Ratu (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2020)
This research aimed to know the structure of economic growth, the level of inequality, and the relationship between economic growth and regional inequality in West Sumatra Province from 2017 to 2019. The data used in this research are secondary data and are sourced from the publication of the Statistics Indonesia (BPS). The analytical method used is the analysis of Klassen typology, Williamson index and the pearson correlation test to see the relationship between economic growth and regional inequality. Based on the results of the research from the typology analysis of Klassen, it shows that there are 7 cities in the province of West Sumatra which are in the advanced and fast developing quadrant, namely Payakumbuh City, Bukittinggi City, Padang City, Solok City, Pariaman City, Sawahlunto City, and Padang Panjang City. Based on the analysis using the Williamson index, the income inequality index is 0.198 and this is still relatively low. There is a strong relationship between economic growth and the level of regional inequality with the opposite direction of the relationship as evidenced by the pearson correlation test.